Reviews of Modern Plasma Physics - Hahm, Taik Soo.; e; Pu, Yi-Kang.; Mima, Kunioki; Lin, Yu.; Shibata, Kazunari; Kikuchi, Mitsuru; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer.)
This international review journal is led by the Division of Plasma Physics of the Association of Asia Pacific Physical Societies. It aims to be a flagship in the field of plasma physics and its application, and to publish cutting-edge reviews and tutorials of modern plasma physics. In particular, selected reviews by leading researchers and seminal reviews by S. Chandrasekhar Prize laureates are published. The journal covers all fields of plasma physics including fundamental and applied physics relevant to natural and laboratory plasmas. Chief among these are: Fundamental physics Nuclear and fusion physics Astrophysics Geophysics Laser science Applied physics Review articles in the journal are characterized not only by their excellent quality, but also their high readability. Therefore the published articles serve as authoritative materials for graduate students and young researchers less familiar with the fields covered.
Keywords: Astronomy; Astrophysics; Cosmology; Nuclear fusion; Plasma (Ionized gases).; Lasers; Photonics; Plasma Physics; Astronomy, Astrophysics and Cosmology; Nuclear Fusion; Optics, Lasers, Photonics, Optical Devices